Concepts of functioning and health important to people with systemic sclerosis: a qualitative study in four European countries. Issue 6 (2nd May 2011) - Stamm, Tanja A; Mattsson, Malin; Mihai, Carina; Stöcker, Juliane; Binder, Alexa; Bauernfeind, Bettina; Stummvoll, Georg; Gard, Gunvor; Hesselstrand, Roger; Sandqvist, Gunnel; Draghicescu, Oana; Gherghe, Ana Maria; et al.
Abstract : Objective: To describe the experiences of people with systemic sclerosis (SSc) in different European countries of functioning and health and to link these experiences to the WHO International Classification of Functioning, Disability and Health (ICF) to develop a common understanding from a bio-psycho-social perspective. Method: A qualitative multicentre study with focus-group interviews was performed in four European countries: Austria, Romania, Sweden and Switzerland. The qualitative data analysis followed a modified form of 'meaning condensation' and the concepts that emerged in the analysis were linked to the ICF. Results: 63 people with SSc participated in 13 focus groups. In total, 86 concepts were identified. 32 (37%) of these were linked to the ICF component body functions and structures, 21 (24%) to activities and participation, 26 (30%) to environmental factors, 6 (7%) to personal factors and 1 (1%) to the health condition itself. 19 concepts (22%) were identified in all four countries and included impaired hand function, household activities, paid work, drugs, climate and coldness, support from others and experiences with healthcare institutions, non-pharmacological treatment, social security and benefits. Conclusion: Concepts identified in all four countries could be used for guiding clinical assessment, as well as interdisciplinary team care and rheumatological rehabilitation for patients with SSc. For a full understanding of the aspects of the disease that were most relevant to people with SSc, people with SSc from multiple countries needed to be involved.